Estimation and application of the thermodynamic properties of aqueous phenanthrene and isomers of methylphenanthrene at high temperature - Dick, Jeffrey; Evans, Katy; Holman, Alex; Jaraula, Caroline; Grice, Kliti (Pergamon-Elsevier Science Ltd, 2013)
Estimates of standard molal Gibbs energy (ΔGf°) and enthalpy (ΔHf°) of formation, entropy (S°), heat capacity (Cp°) and volume (V°) at 25 °C and 1 bar of aqueous phenanthrene (P) and 1-, 2-, 3-, 4- and 9-methylphenanthrene (1-MP, 2-MP, 3-MP, 4-MP, 9-MP) were made by combining reported standard-state properties of the crystalline compounds, solubilities and enthalpies of phenanthrene and 1-MP, and relative Gibbs energies, enthalpies and entropies of aqueous MP isomers from published quantum chemical simulations. The calculated properties are consistent with greater stabilities of the β isomers (2-MP and 3-MP) relative to the α isomers (1-MP and 9-MP) at 25 °C. However, the metastable equilibrium values of the abundance ratios 2-MP/1-MP (MPR) and (2-MP + 3-MP)/(1-MP + 9-MP) (MPI-3) decrease with temperature, becoming <1 at ~375–455 °C. The thermodynamic model is consistent with observations of reversals of these organic maturity parameters at high temperature in hydrothermal and metamorphic settings. Application of the model to data reported for the Paleoproterozoic Here’s Your Chance (HYC) Pb–Zn–Ag ore deposit (McArthur River, Northern Territory, Australia) indicates a likely effect of high-temperature equilibration on reported values of MPR and MPI-3, but this finding is contingent on the location within the deposit. If metastable equilibrium holds, a third aromatic maturity ratio, 1.5 × (2-MP + 3-MP)/(P + 1-MP + 9-MP) (MPI-1), can be used as a proxy for oxidation potential. Values of log aH2(aq) determined from data reported for HYC and for a sequence of deeply buried source rocks are indicative of more reducing conditions at a given temperature than those inferred from data reported for two sets of samples exposed to contact or regional metamorphism. These results are limiting-case scenarios for the modeled systems that do not account for effects of non-ideal mixing or kinetics, or external sources or transport of the organic matter.Nevertheless, quantifying the temperature dependence of equilibrium constants of organic reactions enables the utilization of organic maturity parameters as relative geothermometers at temperatures higher than the nominal limits of the oil window.